Current Status of Antimicrobial Sensitivity Pattern of Streptococcus pneumonia Strains Collected from Clinical Sources in Dhaka, Bangladesh - Shahriar, Mohammad; Madak, Manasi; Haque, Anika; Kabir, Shaila; Saha, Moni Rani (Stamford Journal of Pharmaceutical Sciences, 2011)
A study of antimicrobial sensitivity of Streptococcus pneumoniae strains from clinical specimens was carried out to facilitate the preference of antimicrobial drugs in the management of S. pneumoniae induced infections. The duration of the study was about 12 months starting from March 2009 to March 2010. The results of the study show that tetracycline and chloramphenicol had a low sensitivity (20% and 22%, respectively) to S. pneumoniae while a moderate sensitivity was found for azithromycin (50%), erythromycin (54%), cotrimoxazole (58%), cefuroxime (62%), and cefaclor (62%). However, the highest sensitivity was observed for ceftriaxone (92%) followed by levofloxacin (74%) and ceftazidime (70%). This study reveals the growing antimicrobial resistance in Bangladesh and refers not to use the antimicrobial drugs that show insufficient sensitivity against S. pneumoniae to prevent resistance and associated treatment failure. Key words: Streptococcus pneumoniae; antimicrobial sensitivity; clinical isolates. DOI: 10.3329/sjps.v3i1.6800 S. J. Pharm. Sci. 3(1): 59-62